Roseomonas wenyumeiae sp. nov., isolated from faeces of Tibetan antelopes (Pantholops hodgsonii) on the Qinghai–Tibet Plateau. Issue 10 (30th May 2019) - Tian, Zhi; Lu, Shan; Jin, Dong; Yang, Jing; Pu, Ji; Lai, Xin-He; Wang, Xiao-Xia; Wu, Xiao-Min; Li, Junqin; Wang, Suping; Xu, Jianguo
Abstract : Two Gram-stain-negative, catalase- and oxidase-positive, non-spore-forming, aerobic, motile, flagellated, and coccus-shaped strains (Z23 T and Z24) were isolated from faeces of Tibetan antelopes ( Pantholops hodgsonii ) on the Qinghai–Tibet Plateau, PR China. Results of the morphological, biochemical, and phylogenetic studies indicated that they were similar to each other, but distinct from existing species of the genus Roseomonas . The proposed type strain, Z23 T, had 97.8, 97.1 and 96.8 % 16S rRNA similarity to Roseomonas ludipueritiae DSM 14915 T, Roseomonas aerofrigidensis JCM 31878 T and Roseomonas aerophila KACC 16529 T . Results from further phylogenetic analyses based on the 16S rRNA gene and 857 core genes indicated that the two strains were members of Roseomonas, but clearly separated from the currently recognized species. Strains Z23 T had 43.8 %, 25.0 % DNA–DNA relatedness and 91.2, 81.3 % ANI values with R. ludipueritiae DSM 14915 T and R. aerophila KACC 16529 T . The genomic DNA G+C content of strain Z23 T was 68.6 mol%. The major cellular fatty acids of strain Z23 T were C18 : 1 ω7 c and/or C18 : 1 ω6 c and C19 : 0 cyclo ω 8 c . The cell-wall sugars included glucose, rhamnose and ribose. Q-10 was the sole respiratory quinone, and spermidine was the major polyamine component. Polar lipids present in strain Z23 T were phosphatidylcholine, diphosphatidylglycerol, phosphatidylethanolamine, aminophospholipid, phosphatidylglycerol, three aminolipids, two phospholipids and two unidentified lipids. Based on the distinct differences from other Roseomonas species judged from the genotypic and phenotypic data, a novel species represented by Z23 T and Z24, Roseomonas wenyumeiae sp. nov., is proposed. The type strain is Z23 T (=CGMCC 1.16540 T =DSM 106207 T ).